The Bias Due to Omitting Quality When Estimating Automobile Demand - Trandel, Gregory A. (The Review of Economics and Statistics, 1991)
The conclusions of policy-oriented market studies often hinge upon the size of an estimated demand elasticity. Few of the researchers who have estimated such elasticities have utilized a variable designed to measure the subjective concept of "quality." If quality both significantly affects the demand for a heterogeneous good and is positively correlated with price, omitting quality from a demand regression will lead to a downward bias in the estimated price elasticity. Using Levinsohn's (1988) model of the automobile market as a framework, this note shows that including quality variables can increase the model's estimated price elasticity by more than 80 percent. Copyright 1991 by MIT Press.